Smallwood Interview 01A - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland Educational Television Centre, 1983)
Cathy Boak interviews Joey Smallwood. In this segment they discuss Joey Smallwood's love of reading and his personal library of 18,000 books. Interview takes place in the library of Smallwood's home.